Vapor-liquid equilibria of binary system CO and Cl2 in mixture of greenhouse gases using quantum calculation - Duoc, Nguyen Thanh; Ai Nhung, Nguyen Thi; Duong, Tran; Ngoc Han, Pham Nu; Tat, Pham Van (Vietnam Journal of Chemistry, 2016)
The gases CO and Cl2 presented in atmosphere and mixture of greenhouse gases cause the greenhouse effects in the stratosphere. The COSMO method was applied to calculate the physicochemical properties, quantum-optimum structures and the surface screening charges surrounding the CO and Cl2 molecule by the DFT VWN-BP method with basis set DNP (Double Numerical basis with polarization functions). The segment activity coefficients generated by COSMO-SAC method were used to predict the vapor-liquid equilibria of binary mixture CO(1)-Cl2(2) at different temperatures and pressures. The calculated results were also compared with those from Wilson and NTRL method. They are very close experimental data. The values of RMSE, the mean relative deviation at constant pressure (MRDp) and mean deviation of vapor composition (MDy) in Table 2 are less than 0.012, 5.735 and 0.015, respectively. So the discrepancies between models are insignificant. Keywords. COSMO-SAC method, liquid-vapor equilibria, binary mixture CO and Cl2.